2003
DOI: 10.1002/cncr.11818
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic analysis of chromium accumulation in the bronchi and lung of chromate workers

Abstract: BACKGROUNDIt is known that chromium is an inhaled carcinogen and an important risk factor in the development of lung carcinoma.METHODSThe authors used a microscopic X‐ray fluorescence analyzer with transmitted X‐ray mapping imaging (Horiba, Kyoto, Japan) to measure the accumulation of chromium in 10 resected lung tissue specimens and 90 biopsy specimens from chromate workers.RESULTSThe maximum chromium accumulation (mean ± standard deviation) in 10 resected lung tissue specimens was 197 ± 238 counts per second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 22 publications
1
20
1
Order By: Relevance
“…First of all, total Cr in EBC decreased 15 h after the last exposure, a finding that is in line with previous results observed before and after a weekend, and confirms that Cr can pass through airway lining fluid [11]: the kinetics of pulmonary lung desorption is relatively slow [35], and Cr accumulation has recently been observed in the bronchi and lungs of chromate workers [36]. Most importantly, the EBC Cr(VI) data confirmed that Cr(VI) was reduced to Cr(III) by airway lining fluid, but not completely so (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…First of all, total Cr in EBC decreased 15 h after the last exposure, a finding that is in line with previous results observed before and after a weekend, and confirms that Cr can pass through airway lining fluid [11]: the kinetics of pulmonary lung desorption is relatively slow [35], and Cr accumulation has recently been observed in the bronchi and lungs of chromate workers [36]. Most importantly, the EBC Cr(VI) data confirmed that Cr(VI) was reduced to Cr(III) by airway lining fluid, but not completely so (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The relatively low correlation coeYcients are justiWed by the narrow interval of measured values and the associated high intra-and extra-individual variability. Moreover, many authors have reported that pulmonary tissue Cr levels are not uniform in both exposed and unexposed subjects, and that Cr tends to accumulate in the upper lung areas and bronchi (Raithel et al 1987;Vanoeteren et al 1986;Ishikawa et al 1994;Kondo et al 2003). Although we measured Cr in three diVerent tissue pieces, this non-uniformity may explain the moderate r and r 2 values in our correlation with Cr-EBC (r = 0.55, r 2 = 0.30).…”
Section: Discussioncontrasting
confidence: 65%
“…Occupational exposure to CrVI occurs mainly through inhalation, where considerable quantities are retained in the lungs [Ishikawa et al, 1994;Kondo et al, 2003] leading to respiratory tract problems and lung cancer [Dayan and Paine, 2001].…”
Section: Introductionmentioning
confidence: 99%